2012
DOI: 10.1371/journal.pone.0047535
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower mosaic virus Protein P6 Inhibits Signaling Responses to Salicylic Acid and Regulates Innate Immunity

Abstract: Cauliflower mosaic virus (CaMV) encodes a multifunctional protein P6 that is required for translation of the 35S RNA and also acts as a suppressor of RNA silencing. Here we demonstrate that P6 additionally acts as a pathogenicity effector of an unique and novel type, modifying NPR1 (a key regulator of salicylic acid (SA)- and jasmonic acid (JA)-dependent signaling) and inhibiting SA-dependent defence responses We find that that transgene-mediated expression of P6 in Arabidopsis and transient expression in Nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 68 publications
8
94
0
3
Order By: Relevance
“…Victorin, a toxin produced by the necrotrophic fungus C. victoriae (the causative agent of Victoria blight disease) indirectly targets NPR1 by binding to TRX-h5, which is required for the nuclear localization of NPR1 (Tada et al, 2008). The 2b protein of CMV targets NPR1 to exploit SA-JA antagonism, while the CMV P6 protein interferes with the nuclear localization of NPR1 to suppress SA and activate JA signaling (Lewsey et al, 2010;Love et al, 2012). Syringolin A, a toxin and proteasome inhibitor produced by the bacterial pathogen P. syringae pv syringae, has been proposed to inhibit the degradation of NPR1 (Schellenberg et al, 2010), which is required for the activation of SA-mediated defenses (Spoel et al, 2009).…”
Section: Effectors Targeting Sa Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Victorin, a toxin produced by the necrotrophic fungus C. victoriae (the causative agent of Victoria blight disease) indirectly targets NPR1 by binding to TRX-h5, which is required for the nuclear localization of NPR1 (Tada et al, 2008). The 2b protein of CMV targets NPR1 to exploit SA-JA antagonism, while the CMV P6 protein interferes with the nuclear localization of NPR1 to suppress SA and activate JA signaling (Lewsey et al, 2010;Love et al, 2012). Syringolin A, a toxin and proteasome inhibitor produced by the bacterial pathogen P. syringae pv syringae, has been proposed to inhibit the degradation of NPR1 (Schellenberg et al, 2010), which is required for the activation of SA-mediated defenses (Spoel et al, 2009).…”
Section: Effectors Targeting Sa Signalingmentioning
confidence: 99%
“…P6 is thought to act by altering the expression and localization of NPR1 ( Figure 3) as P6 expressing plants accumulate high levels of NPR1 in the nucleus even in unelicited plants. Thus, it was proposed that an inactive form of NPR1 disrupts NPR1-mediated SA defense gene transcription in the presence of a pathogen that activates SA signaling (Love et al, 2012).…”
Section: Npr1 a Phytohormne Signaling Hub Indirectly Targeted By Patmentioning
confidence: 99%
“…The BSCTV-encoded C2 protein is a silencing suppressor protein that also usurps host UPS processes to promote susceptibility (Zhang et al, 2011). The CaMV-encoded P6 protein suppresses SA-mediated defenses, as well as RNA silencing defenses (Love et al, 2007(Love et al, , 2012. Oftentimes, these viral proteins are recognized by R genes to trigger immune responses.…”
Section: Future Prospects and Considerationsmentioning
confidence: 99%
“…However, the authors could not detect enhanced susceptibility to ORMV in npr1 mutants compared with wild-type plants (Huang et al, 2005). More recent findings demonstrated that Cauliflower mosaic virus (CaMV) P6 alters the expression and sub-cellular localization of NPR1 and inhibits the SAdependent defence responses (Love et al, 2012). Moreover, another recent report showed that SA-induced RDR1 expression is dependent on NPR1 (Hunter et al, 2013).…”
Section: Rna Interference-mediated Resistancementioning
confidence: 94%